2015
DOI: 10.3747/co.22.2532
|View full text |Cite
|
Sign up to set email alerts
|

Patient Preferences for Timing and Access to Radiation Therapy

Abstract: Purpose Patient preferences for radiation therapy (rt) access were investigated. MethodsPatients completing a course of rt at 6 centres received a 17-item survey that rated preferences for time of day; day of week; actual, ideal, and reasonable travel times for rt; and actual, ideal, and reasonable times between referral and first oncologic consultation. Patients receiving single-fraction rt or brachytherapy alone were excluded. ResultsOf the respondents who returned surveys (n = 1053), 54% were women, and 74%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Results of a survey amongst six RT centers showed that patients have different preferences regarding the time of their treatment appointments, with 80% of the patients agreeing that having RT between 08h00 and 16h30 was preferred, while 14%-15% preferred the 07h30-08h00 or the 16h30-17h00 time windows. A further 6% or fewer patients preferred times before 07h30 or after 18h00 [ 6 ]. From a patient’s perspective, research shows that the professional staffing standards and low waiting times for both diagnosis and treatment are the most important factors [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Results of a survey amongst six RT centers showed that patients have different preferences regarding the time of their treatment appointments, with 80% of the patients agreeing that having RT between 08h00 and 16h30 was preferred, while 14%-15% preferred the 07h30-08h00 or the 16h30-17h00 time windows. A further 6% or fewer patients preferred times before 07h30 or after 18h00 [ 6 ]. From a patient’s perspective, research shows that the professional staffing standards and low waiting times for both diagnosis and treatment are the most important factors [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…The growing number of treatment sessions to be booked amongst the available machines makes the scheduling process especially complex for RT centers aiming at delivering timely and patient-friendly treatments. Not only has it been shown that delays in the start of treatment may induce greater psychological distress in patients subject to longer waiting times [ 5 ], but also that 80% of the patients prefer a short interval (2 weeks or less) between referral and first oncology consultation [ 6 ]. The problem of scheduling RT treatment sessions for large varieties of treatment care pathways and technical constraints has been tackled by several studies in the current literature [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…They showed that the quality of care, from a patients’ perspective, increased when patients feel involved into the scheduling process and experience the provider trying to satisfy their personal preferences for the (several) number of visits they must pay to the hospital. Moreover, literature shows that patients have different preferences regarding the time of their appointments, emphasizing the importance of fulfilling those for increased patient-centeredness [ 6 ]. The goal of these RT centers is to schedule irradiation sessions such that all patients start treatment in due time, medical and technological constraints are satisfied, and the fulfilment of patient preferences regarding the starting time of their sessions is maximized.…”
Section: Introductionmentioning
confidence: 99%
“…literature shows that patients have different preferences regarding the time of their appointments, emphasizing the importance of fulfilling those for increased patient-centeredness [70]. The goal of these RT centers is to schedule irradiation sessions such that all patients start treatment in due time, medical and technological constraints are satisfied, and the fulfilment of patient preferences regarding the starting time of their sessions is maximized.…”
Section: Chapter 5 Radiotherapy Treatment Scheduling Considering Time Window Preferencesmentioning
confidence: 99%
“…The growing number of treatment sessions to be booked amongst the available machines makes the scheduling process especially complex for RT centers aiming at delivering timely and patient-friendly treatments. Not only has it been shown that delays in the start of treatment may induce greater psychological distress in patients subject to longer waiting times [63], but also that 80% of the patients prefer a short interval (two weeks or less) between referral and first oncology consultation [70]. The problem of scheduling RT treatment sessions for large varieties of treatment care pathways and technical constraints has been tackled by several studies in the current literature [107].…”
Section: Introductionmentioning
confidence: 99%